2015
DOI: 10.1021/acs.nanolett.5b01785
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Normal and Cancer Cell Adhesion on Custom Designed Protein Nanopatterns

Abstract: Cell adhesion to the extracellular matrix is deregulated in metastasis. However, traditional surfaces used to study cell adhesion do not faithfully mimic the in vivo microenvironment. Electron beam lithography (EBL) is able to generate customized protein nanopatterns. Here, we used an EBL-based green lithography approach to fabricate homogeneous and gradient, single (fibronectin, K-casein) and double (fibronectin, laminin) active component protein nanopatterns with micrometer scale spacing to investigate diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Interestingly, invadopodia formation can be initiated by large distances between certain ligands (i.e., low ligand density), as shown by fibronectin-coated gradient nanopatterns created by electron beam lithography [62]. Similar fibronectin-coated gradient nanopatterns demonstrated that breast cancer cells but not normal mammary cells can adapt flexibly to different ligand densities [63]. Marked cellular flexibility on variable ligand densities was also detected in melanoma cells exposed to Au nanopatterns functionalized with N-or E-cadherin.…”
Section: Modulation Of Tumor Cell Functions By Nanostructured Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, invadopodia formation can be initiated by large distances between certain ligands (i.e., low ligand density), as shown by fibronectin-coated gradient nanopatterns created by electron beam lithography [62]. Similar fibronectin-coated gradient nanopatterns demonstrated that breast cancer cells but not normal mammary cells can adapt flexibly to different ligand densities [63]. Marked cellular flexibility on variable ligand densities was also detected in melanoma cells exposed to Au nanopatterns functionalized with N-or E-cadherin.…”
Section: Modulation Of Tumor Cell Functions By Nanostructured Ligandsmentioning
confidence: 99%
“…The second method that is widely used to create nanopatterns to address biological questions is electron beam lithography (EBL, Figure 2b). This top-down technique uses a focused electron beam to draw nanoscopic patterns on a surface covered with an electron-sensitive layer [62][63][64]. The latter is called a resist.…”
Section: Nanoscale Ligand Control In Experimental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these uniform topographies or micropatterned chemical cues do not mimic well the real ECM. In contrast, ECM in vivo consists of a combination of directional nano‐ and microscale features that are both cell‐adhesive . Very recently, several papers have demonstrated the uniqueness of these multiscale surfaces in regulating cell adhesion, migration, orientation, and differentiation .…”
mentioning
confidence: 99%
“…In contrast, ECM in vivo consists of a combination of directional nano‐ and microscale features that are both cell‐adhesive . Very recently, several papers have demonstrated the uniqueness of these multiscale surfaces in regulating cell adhesion, migration, orientation, and differentiation . It is therefore highly desirable that one can mimic such multiscale surfaces for the better understanding of the cell behavior, and for the development of more efficient and smarter substrates for biomedical engineering applications.…”
mentioning
confidence: 99%